Volume-Spatial Decisions of Buildings and Structures - Bakulin, Evgeniy Anatolievich; Bakulina, Valentyna Michaylivna; Kostyra, Natalia Oleksandrivna (NULES of Ukraine, 2026)
This educational manual outlines the purpose of volume-spatial decisions for buildings and structures [3, 5, 21], aimed at introducing modern scientific concepts [50], ideas, methods, and technologies for computer-aided design of buildings and their complexes [13, 20, 47, 48], in accordance with functional requirements, physical laws, and the principles of architectural aesthetics [32, 35]. The goal is to consolidate and systematize scientific and technical information in the field of design, to impart and develop skills and knowledge in designing buildings and complexes in compliance with functional requirements [7, 11, 14–18, 24] and Ukrainian legal regulations [1, 2], ensuring reliable and safe usage of buildings and structures [9, 42, 45, 46]. The manual is intended to create and maintain environments for humans that provide the most favorable conditions for their existence [6, 11, 19, 29, 32]. This guide is oriented toward the application of the latest design methods in accordance with existing norms and regulations in Ukraine [6–18, 22–26] and the organizational practices of the construction industry [34]. The primary objective is to study and develop housing decisions that ensure healthy and safe living and working environments. It addresses volume-spatial decisions for multiapartment residential buildings, volume-spatial and engineering decisions for frame-monolithic high-rise residential buildings [55], as well as volume-spatial and structural decisions for industrial enterprises [33]. The manual emphasizes the rational use of zoning within production buildings [24], considering their possible integration within the building volume and the logical grouping of areas and zones according to various criteria (level of industrial hazards, fire and explosion risks [12, 36–38, 49], and the optimization of transport and human flows).
Recommended for publication by the Academic Council of the National University of Life Resources and Environmental Sciences of Ukraine (minutes №4 of 22.10. 2025 y.)
Keywords: Volume-Spatial Decisions; Buildings; Structures; architectural aesthetics; application of the latest design methods